2007
DOI: 10.1590/s1516-31802007000100002
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase gene polymorphism and its association with coronary artery disease

Abstract: CONTEXT AND OBJECTIVE: Obstructive coronary artery disease (CAD) is characterized by the deposition of atherosclerotic plaque on the coronary artery wall. Its manifestations depend on interactions between environmental and genetic risk factors. The aim of this work was to analyze the frequency of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism in patients with CAD and its association with plasma homocysteine levels. Risk factors for CAD were also evaluated. DESIGN AND SETTING: Retrospective with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(45 reference statements)
4
5
0
1
Order By: Relevance
“…Polymorphism MTHFR C677T results in thermolability CAD coronary artery disease, SD standard deviation, Hcy homocysteine, MMA methylmalonic acid and enzyme activity reduction, contributing to increase the Hcy concentrations [26]. In the present study, the MTHFR C677T polymorphism was not associated with increased Hcy concentrations, as also reported in other studies with CAD individuals [27,28]. Other investigations showed increased Hcy concentration in carriers of the MTHFR 677TT genotype compared to the other genotypes; however, polymorphism MTHFR C677T was not associated with the development of CAD [25,29,30].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Polymorphism MTHFR C677T results in thermolability CAD coronary artery disease, SD standard deviation, Hcy homocysteine, MMA methylmalonic acid and enzyme activity reduction, contributing to increase the Hcy concentrations [26]. In the present study, the MTHFR C677T polymorphism was not associated with increased Hcy concentrations, as also reported in other studies with CAD individuals [27,28]. Other investigations showed increased Hcy concentration in carriers of the MTHFR 677TT genotype compared to the other genotypes; however, polymorphism MTHFR C677T was not associated with the development of CAD [25,29,30].…”
Section: Discussionsupporting
confidence: 84%
“…However, in line with our observations, Meisel et al [27] did not find a significant influence of the haplotypes MTHFR C677T and A1298C on the Hcy concentrations of CAD individuals. Furthermore, the haplotypes MTHFR A1298C and MTHFR C677T did not present any relation with the presence or the severity of CAD [28], just as in our study.…”
Section: Discussionsupporting
confidence: 71%
“…It was also suggested that C677T polymorphism, independent of altered homocysteine levels, was associated with CAD [27], while others suggested that hyperhomocysteinemia independent of the C677T genotype was linked with increased CAD risk [16,17,28,29], thus highlighting the contribution of other factors in inducing hyperhomocysteinemia in precipitating CAD. These apparently conflicting findings may be reconciled by is differences in ethnicity [13,16,25,26], relatively small sample size [13,17,27] coupled with the failure to control for confounding factors by some of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Em DAC, o alelo polimórfico foi observado significantemente mais freqüente nos pacientes em relação aos controles [10][11][12][13][14]25 . Em estudo brasileiro, o polimorfismo foi associado à gravidade da doença, mas não apresentou distribuição significantemente diferente entre pacientes com e sem DAC 26 .…”
Section: Discussionunclassified